A Bibliometric Analysis about Entrepreneurs’ Satisfaction with Work - Maria Isabel Barreiro RIBEIRO; António José Gonçalves FERNANDES; António Pedro Ribeiro FERNANDES (Communications of International Proceedings, 2021)
Well-being, involvement, commitment or happiness of workers are themes that have produced a growing interest in research in the field of management (Kolodinsky, Ritchie & Kuna, 2018; Lee, Park & Baker, 2018). So, this study was carried out in order to verify findings in the literature such as: the happiness at work enables the attainment of personal and professional goals and contributes to organizational success (Veld & Alfes, 2017); self-employment is highly valued due to the self-determination and autonomy it provides (Benz & Frey, 2008); self-employed individuals have higher levels of job satisfaction but self-employment does not provide a greater satisfaction with life because these workers work more hours and their leisure time is relatively shorter (Zwan, Hessels & Rietveld, 2018). To achieve this objective, a search was carried out on two databases, namely Scopus and Web of Science (WoS) in May 2020, based on the terms "Entrepreneurship", "Happiness" and "Work". In Scopus database, 14 publications were counted and in WoS database, 25 publications were found, of which 6 were duplicated in both databases. A bibliometric analysis was developed using the VOSviewer software version 1.6.15 and the co-occurrence technique of “full-counting” terms was used in order to build a map that shows the association between the different terms and their grouping into clusters of thematic areas based on 33 publications. Two clusters of terms have been identified. The first cluster relates happiness with being an entrepreneur, employee and independent professionally. And, the second cluster relates self-employment with satisfaction with life.
Keywords: Entrepreneurship; Happiness; Work; Bibliometric; Scopus; Web of Science.